2010
DOI: 10.1007/bf03395710
|View full text |Cite
|
Sign up to set email alerts
|

On Misconceptions About Behavior Analysis Among University Students and Teachers

Abstract: Students frequently show misconceptions regarding scientific psychology in general and basic concepts in behavior analysis in particular. We wanted to replicate the study by Lamal (1995)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
25
1
11

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 31 publications
3
25
1
11
Order By: Relevance
“…The current results replicated findings of earlier studies on misconception prevalence (Arntzen, et al, 2010;Furnham & Hughes, 2014) showing that a large number of myths were widely believed. Overall, it seemed that participants were better at identifying Brain Myths compared to Child Developmental myths, though this may be for methodological reasons.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The current results replicated findings of earlier studies on misconception prevalence (Arntzen, et al, 2010;Furnham & Hughes, 2014) showing that a large number of myths were widely believed. Overall, it seemed that participants were better at identifying Brain Myths compared to Child Developmental myths, though this may be for methodological reasons.…”
Section: Discussionsupporting
confidence: 90%
“…Response options were broken down into "Probably" and "Definitely" True or False allowing for greater information to be gleaned regarding the kinds of True and False responses. In addition, the "Don't Know" option improves upon some previous tests as participants could indicate a lack of knowledge, rather than guessing or leaving items unanswered (Arntzen et al, 2010). This followed the same successful format of Furnham and Hughes (2014).…”
Section: Methodsmentioning
confidence: 96%
“…Consistent with past work (Gardner & Hund, 1983), doctoral students were less likely to affirm erroneous claims about psychology compared to either undergraduates or master's students. However, in contrast to Arntzen et al (2010), we found no significant difference in misconception endorsement between master's and undergraduate students. When interpreting these findings, the difference in sample sizes for each group must be considered; the majority of our respondents were doctoral level students.…”
Section: Brief Discussioncontrasting
confidence: 99%
“…It does not seem unthinkable that seeing Skinner as evil, freaky, or fascist could hinder an unbiased view of his ideas, which are still frequently misunderstood (Arntzen, Lokke, Lokke, & Eilertsen, 2010).…”
mentioning
confidence: 99%